Plant breeding - Brown, Jack , 1955-; Caligari, P. D. S. [ (Peter D. S.)]; Campos, Hugo A. , 1968- (John Wiley & Sons, 2014)
This book, Plant Breeding, has it basis in an earlier text entitled An Introduction to Plant Breeding by Jack Brown and Peter Caligari, first published in 2008.